Sustainable Human Resources Management in Polish enterprises - Anna Walczyna; Barbara Celina Mazur; Weronika Wilczewska (Journal of Modern Science, 2023)
Objectives The purpose of this article is to determine the level of application of sustainable human resource management practices in Polish companies.